PERBAIKAN BOCORAN STORM WATER BASIN RESERVOIR DENGAN METODE ANCHOR KNOB SHEET LINNIN DI PERTAMINA RU V - Sulardi Sulardi (Universitas Mulawarman, 2017)
The purpose of this study is to provide an overview of material specifications and working methods of installation of anchor knob sheets (AKS) as an internal protection of concrete storm water basin structure. The research method used in this research is the research method used by case study approach to solve leakage problem in the internal of concrete structure of tub storm water basin in wastewater treatment unit (EWT) PPT. Pertamina RU V Balikpapan. The results show that the specification of HDPE type material is elastomeric reactive polyurethane water proofing (ERPW) which has the function of chemical damage, chemical resistance,onsite weldability, high resistance to chemical damage, long life and low maintenance. The successful application of material specifications and methods of installing HDPE AKS has been replicated as a protection lining system in the demeniralized water plant process unit and is proven to work well and safely.